Retrograde Accretion of a Caribbean Fringing Reef Controlled by Hurricanes and Sea-level Rise - Blanchon, Paul; Richards, Simon; Bernal, Juan Pablo; Cerdeira-Estrada, Sergio; Ibarra, M. Socrates; Corona-Martínez, Liliana; Martell-Dubois, Raúl (Frontiers in Earth Science, 2017)
Predicting the impact of sea-level (SL) rise on coral reefs requires reliable models of reef accretion. Most assume that accretion results from vertical growth of coralgal framework, but recent studies show that reefs exposed to hurricanes consist of layers of coral gravel rather than in-place corals. New models are therefore needed to account for hurricane impact on reef accretion over geological timescales. To investigate this geological impact, we report the configuration and development of a 4-km-long fringing reef at Punta Maroma along the northeast Yucatan Peninsula. Satellite-derived bathymetry shows the crest is set-back a uniform distance of 315 ±15 m from a mid-shelf slope break, and the reef-front decreases 50% in width and depth along its length. A 12-core drill transect constrained by multiple 230Th ages shows the reef is composed of an ~ 2-m thick layer of coral clasts that has retrograded 100 m over its back-reef during the last 5.5 ka. These findings are consistent with a hurricane-control model of reef development where large waves trip and break over the mid-shelf slope break, triggering rapid energy dissipation and thus limiting how far upslope individual waves can fragment corals and redistribute clasts. As SL rises and water depth increases, energy dissipation during wave-breaking is reduced, extending the clast-transport limit, thus leading to reef retrogradation. This hurricane model may be applicable to a large sub-set of fringing reefs in the tropical Western-Atlantic necessitating a reappraisal of their accretion rates and response to future SL rise.